(untitled) (Journal of Economic Additions, 2025)
This study aims to clarify the factors influencing the gap between accounting practices and their legislative and regulatory framework in Algeria. This study addresses the question: What are these factors and how they are reflected in practice? To achieve this goal, scientific research tools were employed, includingfield interviews, observation, and statistical data processing usingasurvey of a sample of professionals and executives from economic institutions in Algeria. After analyzing the results and testing the hypotheses, it was concluded that the flaw in accounting practices is primarily due to political interference in the accounting organization and profession, as well as the lack of involvement of relevant stakeholders in decision-making. Jel Classification Codes : M40؛ M41؛K34 ؛D73 ؛Q43 .